Absorber
By using water-absorbing resin particles A based on the Vortex method in the absorber, the gel block phenomenon caused by the fast water absorption rate and the problem of too slow absorption rate and countercurrent caused by the slow water absorption rate are solved, and the effects of excellent liquid diffusion, small countercurrent and fast absorption rate are achieved.
Patent Information
- Application Number
- CN202180060656.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-17
- Filing Date
- 2021-06-30
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-06-30
AI Technical Summary
The existing absorber is prone to gel blocking in water-absorbing resin particles with fast water absorption speed, resulting in reduced diffusion and leakage of liquids; while the water-absorbing resin particles with slow water absorption speed absorb liquids too slowly and are prone to countercurrent.
The water-absorbent resin particles A based on the Vortex method have a water absorption rate of 55 seconds to 150 seconds, a 5-minute value of the unpressurized DW is 36 mL/g or less, and a content of 9 mass% to 90 mass%, to take into account liquid diffusion, counterflow rate and absorption rate.
The liquid in the absorber has excellent diffusion properties, low counterflow and fast absorption speed, effectively suppresses gel blocking and improves the utilization rate of the absorber.
Smart Images

Figure CN116133628B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to absorbent bodies. Background Art
[0002] Conventionally, absorbent bodies containing water-absorbent resin particles have been used in absorbent articles for absorbing liquids mainly composed of water, such as urine. For example, Patent Document 1 discloses a method for producing water-absorbent resin particles having a particle size preferably used in absorbent articles such as diapers, and Patent Document 2 discloses a method for using a hydrogel-forming water-absorbent polymer having specific saline flow induction properties, performance under pressure, etc. as an absorbent member for effectively accommodating aqueous body fluids.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 06-345819
[0006] Patent Document 2: Japanese Patent Publication No. 09-510889 Summary of the invention
[0007] (Problem to be solved by the invention)
[0008] As a performance required of absorbent articles, it is important that liquid leakage is difficult to occur even if worn for a long time. As a method of suppressing liquid leakage, it is considered to use water-absorbent resin particles with a fast water absorption rate (large water retention after water absorption) as the constituent material of the absorbent. However, since the liquid diffusivity of the water-absorbent resin particles with a fast water absorption rate is poor, it is ultimately impossible to fully suppress the leakage of liquid from the absorbent article. Specifically, when the water-absorbent resin particles swell due to liquid, the gaps originally existing between the water-absorbent resin particles are filled with the swollen gel-like water-absorbent resin particles, making it difficult for liquid to pass through the gaps. This phenomenon is generally referred to as gel retardation. As a result, the liquid diffusivity in the absorbent is reduced, all the water-absorbent resin particles contained in the absorbent cannot be effectively utilized, and the liquid that is not absorbed by the water-absorbent resin particles is easy to leak from the absorbent.
[0009] In order to suppress the gel block phenomenon, when water-absorbent resin particles with a slow water absorption rate (small water retention after water absorption) are used as the constituent material of the absorbent, the gel block phenomenon is unlikely to occur and the liquid is easy to diffuse in the absorbent. However, when water-absorbent resin particles with a slow water absorption rate are used, the speed at which the absorbent absorbs liquid (absorption rate) tends to become too slow. In addition, water-absorbent resin particles with a slow water absorption rate are prone to liquid backflow (liquid temporarily absorbed by the water-absorbent resin particles leaks) due to pressure.
[0010] An object of the present invention is to provide an absorbent having excellent liquid diffusibility, a small amount of backflow, and a fast absorption rate.
[0011] (Solution to the problem)
[0012] One aspect of the present invention relates to an absorbent body containing water-absorbent resin particles, wherein the water-absorbent resin particles contain water-absorbent resin particles A having a water absorption rate of 55 seconds to 150 seconds based on a Vortex method and a 5-minute value of unpressurized DW of 36 mL / g or less, and the content of the water-absorbent resin particles A is 9% to 90% by mass based on the total amount of the water-absorbent resin particles.
[0013] (Effects of the Invention)
[0014] According to the present invention, it is possible to provide an absorbent body having excellent liquid diffusibility, a small amount of backflow, and a fast absorption rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a cross-sectional view showing an example of an absorbent article.
[0016] Figure 2 It is a schematic diagram showing a measuring device of the non-pressurized DW of the water-absorbing resin particles. DETAILED DESCRIPTION
[0017] Hereinafter, some embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments.
[0018] In this specification, "acrylic acid" and "methacrylic acid" are combined and marked as "(meth)acrylic acid". "Acrylate" and "methacrylate" are also marked as "(meth)acrylate". "(Poly)" refers to both the case of having the prefix "poly" and the case of not having the prefix "poly". In the numerical ranges recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range of other stages. In the numerical ranges described in this specification, the upper limit or lower limit of its numerical range can be replaced by the value shown in the embodiment. The materials exemplified in this specification can be used alone or in combination of two or more. Regarding the content of each component in the composition, when there are multiple substances corresponding to each component in the composition, unless otherwise specified, it refers to the total amount of the multiple substances present in the composition. "Room temperature" refers to 25±2°C. When viewed from a top view, in addition to the shape structure formed on the entire surface, the term "layer" also includes a shape structure formed on a part. "Physiological saline" refers to a 0.9 mass % sodium chloride aqueous solution.
[0019] [Absorber]
[0020] The absorbent body according to the present embodiment includes water-absorbent resin particles containing water-absorbent resin particles A having a water absorption rate of 55 to 150 seconds based on the Vortex method and a 5-minute value of DW without pressure of 36 mL / g or less. The content of the water-absorbent resin particles A in the absorbent body is 9 to 90% by mass based on the total amount of the water-absorbent resin particles.
[0021] When the water absorption rate of the water-absorbent resin particles A is 55 seconds or more, the occurrence of gel retardation phenomenon is easily suppressed. When the water absorption rate of the water-absorbent resin particles A is 150 seconds or less, the water absorbency is excellent and the dry feeling is easily improved. From the viewpoint of more easily reflecting the effect exerted by the present invention, the water absorption rate of the water-absorbent resin particles A can be 58 seconds or more, 60 seconds or more, or 61 seconds or more, preferably 63 seconds or more, 65 seconds or more, or 67 seconds or more. In addition, the water absorption rate can be 130 seconds or less, 110 seconds or less, or 90 seconds or less, preferably 80 seconds or less, 75 seconds or less, or 70 seconds or less. The water absorption rate based on the Vortex method is measured in accordance with JIS K 7224 (1996) as described in the examples described later.
[0022] When the 5-minute value of the non-pressurized DW of the water-absorbent resin particles A is 36 mL / g or less, the diffusivity of urine is increased by preserving the water absorption amount at the initial stage of water absorption, thereby improving the absorption speed and the utilization rate of the absorbent body (the utilization rate of the entire water-absorbent resin particles contained in the absorbent body). The 5-minute value of the non-pressurized DW of the water-absorbent resin particles A can be 35 mL / g or less, 34 mL / g or less, or 33 mL / g or less, preferably 30 mL / g or less, 20 mL / g or less, or 15 mL / g or less, and more preferably 10 mL / g or less, 8 mL / g or less, or 5 mL / g or less, from the perspective of taking into account both excellent liquid diffusivity and excellent backflow. The lower limit of the 5-minute value of the non-pressurized DW can be 1 mL / g or more. The 5-minute value of the non-pressurized DW is measured by the method described in the embodiments described later. The 5-minute value of the unpressurized DW is the water absorption rate expressed by the amount of saline absorbed by the water-absorbent resin particles after 5 minutes from contact with saline without pressure. The unpressurized DW is expressed by the absorption amount [mL] per 1 g of the water-absorbent resin particles before absorption of saline.
[0023] The physiological saline water retention (water retention) of the water-absorbent resin particles A can be, for example, 16 g / g or more, 18 g / g or more, or 20 g / g or more, from the viewpoint of being easier to achieve both excellent liquid diffusivity and excellent backflow. The physiological saline water retention can be 50 g / g or less, 45 g / g or less, or 40 g / g or less, preferably 35 g / g or less or 30 g / g or less, and more preferably 25 g / g or less or 22 g / g or less. The physiological saline water retention is measured by the method described in the Examples described below.
[0024] The absorbent according to the present embodiment contains 9% to 90% by mass of the water-absorbent resin particles A based on the total amount of the water-absorbent resin particles, thereby achieving excellent liquid diffusivity, low backflow rate, and rapid absorption rate. From the perspective of excellent backflow rate and rapid absorption rate, the content of the water-absorbent resin particles A can be 10% by mass or more, 12% by mass or more, or 16% by mass or more, preferably 20% by mass or more, 30% by mass or more, or 33% by mass or more, and more preferably 50% by mass or more, 55% by mass or more, 60% by mass or more, or 66% by mass or more. From the perspective of achieving both excellent liquid diffusivity and rapid absorption rate, the content of the water-absorbent resin particles A can be 88% by mass or less, 86% by mass or less, 85% by mass or less, or 84% by mass or less.
[0025] The structure of the water-absorbing resin particles A is not particularly limited as long as the resin satisfies the above-mentioned water absorption rate and 5-minute value of unpressurized DW. The water-absorbing resin particles A may be, for example, coated resin particles having a water-insoluble coating layer coating at least a portion of the surface of the water-absorbing resin particles.
[0026] The water-absorbent resin particles constituting the coated resin particles are not particularly limited as long as they are composed of a resin having water absorption, and for example, may include a cross-linked polymer formed by polymerization of a monomer containing an ethylenically unsaturated monomer. The cross-linked polymer may have a monomer unit derived from an ethylenically unsaturated monomer. For example, the water-absorbent resin particles may be prepared by a method including a step of polymerizing a monomer containing an ethylenically unsaturated monomer. Examples of the polymerization method include reverse phase suspension polymerization, aqueous solution polymerization, bulk polymerization, precipitation polymerization, and the like.
[0027] The ethylenically unsaturated monomer may be a water-soluble ethylenically unsaturated monomer (an ethylenically unsaturated monomer having a solubility of 1 g or more in 100 g of water at 98° C.). Examples of the water-soluble ethylenically unsaturated monomer include (meth)acrylic acid and salts thereof, 2-(meth)acrylamide-2-methylpropanesulfonic acid and salts thereof, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylate, N-hydroxymethyl(meth)acrylamide, polyethylene glycol mono(meth)acrylate, N,N-diethylaminoethyl(meth)acrylate, N,N-diethylaminopropyl(meth)acrylate, diethylaminopropyl(meth)acrylamide, and the like. When the ethylenically unsaturated monomer has an amino group, the amino group may be quaternized. The ethylenically unsaturated monomer may be used alone or in combination of two or more.
[0028] When the ethylenically unsaturated monomer has an acid group, the acid group can be neutralized by an alkaline neutralizing agent and then used for polymerization. The degree of neutralization of the ethylenically unsaturated monomer by the alkaline neutralizing agent can be, for example, 10 mol% to 100 mol%, 50 mol% to 90 mol%, or 60 mol% to 80 mol% of the acid group in the ethylenically unsaturated monomer.
[0029] From the viewpoint of industrial availability, the ethylenically unsaturated monomer may include at least one compound selected from the group consisting of (meth)acrylic acid and its salts, acrylamide, methacrylamide, and N,N-dimethylacrylamide. The ethylenically unsaturated monomer may include at least one compound selected from the group consisting of (meth)acrylic acid and its salts, and acrylamide.
[0030] As the monomer for obtaining the water-absorbent resin particles, monomers other than the above-mentioned ethylenically unsaturated monomers can be used. Such monomers can be mixed with an aqueous solution containing the above-mentioned ethylenically unsaturated monomers for use. The amount of the ethylenically unsaturated monomers used can be 70 mol % to 100 mol % relative to the total amount of monomers. The proportion of (meth) acrylic acid and its salts can be 70 mol % to 100 mol % relative to the total amount of monomers.
[0031] Crosslinking may occur due to self-crosslinking during polymerization, but crosslinking can be promoted by using an internal crosslinking agent. When an internal crosslinking agent is used, it is easy to control the water absorption characteristics (water retention, etc.) of the water-absorbent resin particles. The internal crosslinking agent is usually added to the reaction solution during the polymerization reaction.
[0032] The water-absorbent resin particles may be particles that are cross-linked near the surface (surface cross-linking). Furthermore, the water-absorbent resin particles are composed only of polymer particles (cross-linked polymers), but may further contain various additional components selected from, for example, gel stabilizers, metal chelating agents, and fluidity enhancers (lubricants). The additional components may be placed inside the polymer particles, on the surface of the polymer particles, or both. The additional components may be a fluidity enhancer (lubricant). The fluidity enhancer may contain inorganic particles. As inorganic particles, for example, silica particles such as amorphous silica may be cited.
[0033] The shape of the water-absorbent resin particles is not particularly limited, and may be, for example, substantially spherical, crushed, or granular, or may be a shape in which primary particles having such shapes are aggregated.
[0034] The median particle size of the water-absorbent resin particles may be 100 to 800 μm, 150 to 700 μm, 200 to 600 μm, or 250 to 500 μm. The median particle size can be measured by the following method.
[0035] <Method for measuring median particle size>
[0036] A sieve with a mesh size of 600 μm, a sieve with a mesh size of 500 μm, a sieve with a mesh size of 425 μm, a sieve with a mesh size of 300 μm, a sieve with a mesh size of 250 μm, a sieve with a mesh size of 180 μm, a sieve with a mesh size of 150 μm, and a tray were sequentially combined from top to bottom as JIS standard sieves. 50 g of water-absorbent resin particles were placed in the uppermost sieve of the combination and classified using a Ro-Tap type vibrator (manufactured by Iida Seisakusho Co., Ltd.) in accordance with JIS Z 8815 (1994). After classification, the mass of particles remaining on each sieve was calculated as a mass percentage relative to the total mass to obtain the particle size distribution. For this particle size distribution, the ratio of the mass percentage of the particles remaining on the sieve is accumulated in order from the larger particle size, and the relationship between the sieve mesh size and the cumulative value of the ratio of the mass percentage of the particles remaining on the sieve is plotted on the logarithmic probability paper. By connecting the plotted points on the probability paper with a straight line, the particle size corresponding to the cumulative mass percentage of 50% can be taken as the median particle size.
[0037] The water-insoluble coating layer constituting the coated resin particles is a layer containing a water-insoluble component. In this specification, the water-insoluble component may include not only a substance that is completely insoluble in water but also a substance that is slightly soluble in water (a water-poorly soluble substance). The solubility of the water-insoluble component in 100 g of water is, for example, less than 10 g at 98° C., preferably less than 5 g, more preferably less than 3 g, and further preferably less than 1 g.
[0038] The coating layer may be a layer containing at least one water-insoluble component selected from the group consisting of water-insoluble organic compounds and water-insoluble inorganic compounds.
[0039] As the water-insoluble organic compound, for example, polyurethane, polyolefin, polyester, polyamide, polystyrene, polycarbonate, polyacrylate, polyacetal and their acid-modified products can be cited. Preferably, the water-insoluble organic compound contains at least one selected from the group consisting of polyolefin, polyurethane, polyester and their acid-modified products, more preferably, contains at least one selected from the group consisting of polyolefin, polyurethane and their acid-modified products, and further preferably, contains acid-modified polyolefin and / or polyurethane. The organic compound can be used alone or in combination of multiple types.
[0040] When the water-insoluble component is acid-modified, the water-insoluble component can be modified by at least one acid anhydride selected from the group consisting of maleic anhydride, succinic anhydride and phthalic anhydride. The object of modification by the acid anhydride is preferably a polyolefin, more preferably at least one selected from the group consisting of polyethylene, polypropylene and ethylene-propylene copolymer, and further preferably an ethylene-propylene copolymer. In addition, the acid anhydride used for modification is preferably maleic anhydride.
[0041] Polyurethane is a reaction product of a polyol and a polyisocyanate. Examples of the polyol include polyether polyols, polyester polyols, polybutadiene polyols, hydrogenated polybutadiene polyols, and the like. Examples of the polyisocyanate include aromatic isocyanates such as diphenylmethane diisocyanate, dimethyldiphenylmethane diisocyanate, toluene diisocyanate, xylene diisocyanate, and p-phenylene diisocyanate; alicyclic isocyanates such as dicyclohexylmethane diisocyanate and isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate.
[0042] As water-insoluble inorganic compounds, for example, light anhydrous silicic acid, calcium silicate, silicon dioxide (silica), talc, silicon monoxide and synthetic hydrotalcite can be cited. These inorganic compounds can be used alone or in combination. When forming a coating layer, it can show relatively high water permeability, so preferably, at least one of silicon dioxide and talc is used, and more preferably, silicon dioxide is used. Silica can be hydrophilic or hydrophobic, but since it can easily reach the water absorption rate of the water-absorbent resin particles as described above and the 5-minute value of DW without pressurization, it is preferably hydrophobic.
[0043] When forming a coating layer on the water-absorbent resin particles, the coating layer can be formed on at least a portion of the surface of the water-absorbent resin particles by mixing the water-absorbent resin particles and the coating material. For example, the coating material is a component capable of forming the coating layer as described above or a material forming the component. For example, when the coating layer includes polyurethane, the coating material may include polyurethane itself, or may include polyols and polyisocyanates as materials forming the polyurethane.
[0044] The method for forming the coating layer is not particularly limited. For example, after the water-absorbent resin particles are in a dispersed state, the coating layer can be formed by contacting the water-absorbent resin particles in a dispersed state with the coating material. Specifically, in the case where the coating material is dissolved in the dispersion medium in which the polymer particles are dispersed, the water-absorbent resin particles and the coating material can be added to the dispersion medium to form a coating layer on the surface of the water-absorbent resin particles. In addition, when polyols and polyisocyanates are used as coating materials, an aqueous solution of the polyol can be mixed in the dispersion liquid of the water-absorbent resin particles, so that the water-absorbent resin particles are contacted with the polyol, and then a liquid containing the polyisocyanate is mixed, so that the polyol and the polyisocyanate are polymerized to form a coating layer containing polyurethane on the surface of the polymer particles.
[0045] The dispersion medium may contain a hydrocarbon solvent. Examples of the hydrocarbon solvent include: chain aliphatic hydrocarbons such as n-hexane, n-heptane, 2-methylhexane, 3-methylhexane, 2,3-dimethylpentane, 3-ethylpentane, and n-octane; alicyclic hydrocarbons such as cyclohexane, methylcyclohexane, cyclopentane, methylcyclopentane, trans-1,2-dimethylcyclopentane, cis-1,3-dimethylcyclopentane, and trans-1,3-dimethylcyclopentane; and aromatic hydrocarbons such as benzene, toluene, and xylene.
[0046] When a solid inorganic compound is used as a coating material, the coating material can be pressed onto the surface of the water-absorbent resin particles using a particle composite device to form a coating layer. Specifically, a predetermined amount of water-absorbent resin particles and a solid inorganic compound are put into the particle composite device. Then, by rotating the stirring blades provided on the device, stress (compression stress and shear stress) is applied to the water-absorbent resin particles and the inorganic compound, and by the stress, the inorganic compound is pressed onto the surface of the water-absorbent resin particles to prepare coated resin particles.
[0047] The absorbent according to the present embodiment contains water-absorbent resin particles B which are different from the water-absorbent resin particles A. The water absorption rate based on the Vortex method or the 5-minute value of the non-pressurized DW of the water-absorbent resin particles B is different from that of the water-absorbent resin particles A. As the water-absorbent resin particles B, existing water-absorbent resin particles can be used, for example, water-absorbent resin particles before forming a coating layer by coating the resin particles as described above can be used.
[0048] The water absorption capacity of the water-absorbent resin particles B is not particularly limited as long as at least one of the water absorption rate based on the Vortex method and the 5-minute value of the non-pressurized DW is different from that of the water-absorbent resin particles A. The water-absorbent resin particles B satisfy at least one of the following conditions: the water absorption rate based on the Vortex method is less than 55 seconds, the water absorption rate based on the Vortex method is greater than 150 seconds, or the 5-minute value of the non-pressurized DW is greater than 36 mL / g.
[0049] The water absorption rate of the water-absorbent resin particles B according to the Vortex method may be, for example, 20 seconds or more or 25 seconds or more, 160 seconds or less, 155 seconds or less, or 153 seconds or less, 60 seconds or less, 55 seconds or less, or 53 seconds or less. The 5-minute value of the non-pressurized DW of the water-absorbent resin particles B may be 5 mL / g or more or 9 mL / g or more, preferably 35 mL / g or more, 38 mL / g or more, 40 mL / g or more, or 45 mL / g or more, and more preferably 50 mL / g or more or 54 mL / g or more. The 5-minute value of the non-pressurized DW of the water-absorbent resin particles B may be 65 mL / g or less or 60 mL / g or less, and preferably 55 mL / g or less or 54 mL / g or less.
[0050] The physiological saline water retention capacity of the water-absorbent resin particles B may be 35 g / g or more, 38 g / g or more, or 40 g / g or more, and may be 60 g / g or less, 55 g / g or less, or 50 g / g or less.
[0051] The absorbent according to the present embodiment may include fibrous material, for example, a mixture of water-absorbent resin particles and fibrous material. The absorbent may be composed of, for example, a uniform mixture of water-absorbent resin particles and fibrous material, a sheet-like or layer-like fibrous material with water-absorbent resin particles sandwiched therebetween, or other compositions.
[0052] Examples of the fibrous material include finely ground wood pulp, cotton, cotton linters, rayon, cellulose fibers such as cellulose acetate, synthetic fibers such as polyamide, polyester, and polyolefin, and mixtures of these fibers. The fibrous material may be used alone or in combination of two or more. As the fibrous material, a hydrophilic fiber may be used.
[0053] In order to improve the shape retention of the absorbent before and during use, the fibers can be bonded to each other by adding an adhesive binder to the fibrous material. As the adhesive binder, heat-sealed synthetic fibers, hot-melt adhesives, adhesive emulsions, etc. can be cited. The adhesive binder can be used alone or in combination of two or more.
[0054] As heat-sealable synthetic fibers, for example, there can be listed: full-melt adhesives such as polyethylene, polypropylene, ethylene-propylene copolymers, etc.; non-full-melt adhesives consisting of a side-by-side or core-sheath structure of polypropylene and polyethylene. In the above-mentioned non-full-melt adhesives, only the polyethylene portion can be heat-sealed.
[0055] As hot-melt adhesives, for example, mixtures of base polymers such as ethylene-vinyl acetate copolymers, styrene-isoprene-styrene block copolymers, styrene-butadiene-styrene block copolymers, styrene-ethylene-butylene-styrene block copolymers, styrene-ethylene-propylene-styrene block copolymers, and amorphous polypropylene with thickeners, plasticizers, antioxidants, and the like can be listed.
[0056] Examples of the adhesive emulsion include polymers of at least one monomer selected from the group consisting of methyl methacrylate, styrene, acrylonitrile, 2-ethylhexyl acrylate, butyl acrylate, butadiene, ethylene, and vinyl acetate.
[0057] The absorbent according to the present embodiment may contain inorganic powder (e.g., amorphous silica), deodorant, antibacterial agent, pigment, dye, fragrance, binder, etc. When the water absorbent resin particles contain inorganic particles, the absorbent may contain inorganic powder different from the inorganic particles in the water absorbent resin particles.
[0058] The shape of the absorbent according to the present embodiment may be, for example, a sheet-like shape. The thickness of the absorbent (for example, the thickness of the sheet-like absorbent) may be 0.1 mm to 20 mm or 0.3 mm to 15 mm.
[0059] [Absorbent articles]
[0060] The absorbent article according to the present embodiment has the absorbent body of the present embodiment. As other components of the absorbent article, a core wrap that prevents the components of the absorbent body from falling off or flowing while maintaining the shape of the absorbent body; a liquid-permeable sheet disposed on the outermost side of the liquid-absorbing object on the liquid-immersing side; a liquid-impermeable sheet disposed on the outermost side opposite to the liquid-immersing side of the liquid-absorbing object, etc. Examples of the absorbent article include diapers (e.g., paper diapers), toilet training pants, incontinence pads, sanitary materials (sanitary napkins, sanitary napkins, etc.), sweat-removing pads, absorbent sheets for pets, simple toilet parts, animal excrement disposal materials, etc.
[0061] Figure 1 is a cross-sectional view showing an example of an absorbent article. Figure 1The absorbent article 100 shown includes an absorbent body 10, core wrapping sheets 20a, 20b, a liquid-permeable sheet 30, and a liquid-impermeable sheet 40. In the absorbent article 100, the liquid-impermeable sheet 40, the core wrapping sheet 20b, the absorbent body 10, the core wrapping sheet 20a, and the liquid-permeable sheet 30 are stacked in this order. Figure 1 Although there are portions shown with gaps between components, the components may be in close contact with each other without the gaps.
[0062] The absorbent body 10 has water-absorbent resin particles 10a and a fiber layer 10b including a fibrous material. The water-absorbent resin particles 10a are dispersed in the fiber layer 10b. The water-absorbent resin particles 10a are a mixture of water-absorbent resin particles A and water-absorbent resin particles B.
[0063] The core wrapping sheet 20a is provided on one side of the absorbent body 10 in a state of contact with the absorbent body 10 ( Figure 1 The core wrapping sheet 20b is disposed on the other side of the absorbent body 10 in a state of contact with the absorbent body 10 ( Figure 1 The absorbent body 10 is disposed between the core wrapping sheet 20a and the core wrapping sheet 20b. Examples of the core wrapping sheets 20a and 20b include tissue paper, nonwoven fabric, woven fabric, synthetic resin film having liquid permeable holes, and mesh sheets having meshes. The core wrapping sheet 20a and the core wrapping sheet 20b have, for example, a main surface of the same size as the absorbent body 10.
[0064] The liquid-permeable sheet 30 is disposed on the outermost side of the absorption object on the liquid intrusion side. The liquid-permeable sheet 30 is disposed on the core wrapping sheet 20a in a state of contact with the core wrapping sheet 20a. Examples of the liquid-permeable sheet 30 include nonwoven fabrics and porous sheets formed of synthetic resins such as polyethylene, polypropylene, polyester, and polyamide.
[0065] The liquid-impermeable sheet 40 is disposed on the outermost portion of the absorbent article 100 on the opposite side to the liquid-permeable sheet 30. The liquid-impermeable sheet 40 is disposed on the lower side of the core wrapping sheet 20b in contact with the core wrapping sheet 20b. Examples of the liquid-impermeable sheet 40 include sheets made of synthetic resins such as polyethylene, polypropylene, and polyvinyl chloride, and sheets made of composite materials of the synthetic resin and nonwoven fabrics.
[0066] The liquid-permeable sheet 30 and the liquid-impermeable sheet 40 have main surfaces wider than the main surface of the absorbent body 10, for example, and their outer edges extend around the absorbent body 10 and the core wrapping sheets 20a, 20b.
[0067] The size relationship between the absorbent body 10, the core wrapping sheets 20a, 20b, the liquid-permeable sheet 30 and the liquid-impermeable sheet 40 is not particularly limited and can be appropriately adjusted according to the purpose of the absorbent article. In addition, the method of using the core wrapping sheets 20a, 20b to maintain the shape of the absorbent body 10 is not particularly limited, such as Figure 1 As shown, the absorbent body may be surrounded by a plurality of core wrapping sheets or by a single core wrapping sheet.
[0068] The lower limit of the diffusion length of the absorbent article using the absorbent body according to the present embodiment may be 25 cm or more, 28 cm or more, or 30 cm or more, and the upper limit of the diffusion length may be 40 cm or less or 35 cm or less. The upper limit of the backflow amount of the absorbent article may be 4.0 g or less, 3.0 g or less, 2.0 g or less, or 1.0 g or less, and the lower limit of the backflow amount may be 0.01 g or 0.05 g. The upper limit of the absorption speed of the absorbent article may be 65 seconds or less, 60 seconds or less, 55 seconds or less, or 50 seconds or less, and the lower limit of the absorption speed may be 1 second or more, 5 seconds or more, or 10 seconds or more. The lower limit of the diffusion area of the absorbent article may be 300 cm 2 Above, 315cm 2 Above, 350cm 2 Above, or 400cm 2 Above, the upper limit of the diffusion area can be 480cm 2 Below or 450cm 2 The various properties of the absorbent articles described above were measured by the methods described in the examples described later.
[0069] [Example]
[0070] Hereinafter, the present invention will be described in further detail with reference to Examples, but the present invention is not limited to these Examples.
[0071] [Preparation of water-absorbent resin particles]
[0072] (Preparation Example 1)
[0073] A round-bottomed cylindrical separable flask with an inner diameter of 11 cm and an internal volume of 2 L was prepared, which was equipped with a reflux cooler, a dropping funnel, a nitrogen inlet tube and an agitator. As an agitator, an agitator including a stirring blade with four inclined blades having a blade diameter of 5 cm in two stages was used. 293 g of n-heptane and 0.736 g of maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., Hi-WAX 1105A) as a dispersant were added to the flask and mixed. The mixture in the flask was stirred at 300 rpm while the temperature was raised to 80° C. to dissolve the dispersant in n-heptane, and then the resulting solution was cooled to 50° C.
[0074] 92.0 g of an 80.5 mass % acrylic acid aqueous solution (acrylic acid: 1.03 mol) as a water-soluble ethylenically unsaturated monomer was added to a beaker having an internal volume of 300 mL, and 147.7 g of a 20.9 mass % sodium hydroxide aqueous solution was dripped into the beaker while cooling from the outside to neutralize 75 mol % of the acrylic acid. Subsequently, 0.092 g of hydroxyethyl cellulose (Sumitomo Seika Co., Ltd., HEC AW-15F) as a thickener, 0.0736 g (0.272 mmol) of potassium persulfate as a radical polymerization initiator, and 0.010 g (0.057 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were added and dissolved to prepare a first-stage aqueous solution.
[0075] The aqueous solution of the first stage is added to the separable flask as described above, and then stirred for 10 minutes. Next, a surfactant solution prepared by dissolving 0.736 g of sucrose stearate (Mitsubishi Chemical Foods Co., Ltd., Ryoto Sugar Ester, S-370, HLB: 3) as a surfactant in 6.62 g of n-heptane is added to the flask to obtain a reaction solution. The reaction solution is stirred at a stirrer speed of 550 rpm while the system is fully replaced with nitrogen. Then, the flask is immersed in a water bath at 70°C, the reaction solution is heated, and a polymerization reaction is carried out for 60 minutes to obtain a first-stage polymerization slurry.
[0076] 128.8 g of an 80.5 mass % acrylic acid aqueous solution (acrylic acid: 1.43 mol) was added to a beaker having an internal volume of 500 mL, and 159.0 g of a 27 mass % sodium hydroxide aqueous solution was added dropwise while cooling from the outside to neutralize 75 mol % of the acrylic acid. 0.103 g (0.381 mmol) of potassium persulfate as a radical polymerization initiator and 0.0116 g (0.067 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were added to the beaker to dissolve them, thereby preparing an aqueous solution of the second stage.
[0077] While stirring at a stirrer speed of 1000 rpm, the first-stage polymerization slurry in the flask was cooled to 25°C, and all the second-stage aqueous solution was added. After replacing the interior of the flask with nitrogen for 30 minutes, the flask was immersed in a 70°C water bath again to heat the reaction solution, and the second-stage polymerization reaction was carried out for 60 minutes to obtain a hydrogel polymer. Next, the flask was immersed in an oil bath set at 125°C, and 257.7g of water was extracted out of the system by azeotropic distillation of n-heptane and water. Next, 4.42g (0.507 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a surface crosslinking agent was added to the flask and kept at 83°C for two hours.
[0078] The flask was immersed in an oil bath at 125°C to remove (dry) the n-heptane to obtain polymer particles (dried product). The polymer particles were passed through a 850 μm JIS standard sieve to obtain 228.0 g of water-absorbent resin particles B1. The above operation was repeated to prepare 2 kg of water-absorbent resin particles B1 having a median particle size of 352 μm.
[0079] (Preparation Example 2)
[0080] 80 g of mixed solution 1 of 4 g of polyether polyol (AGC, EXCENOL 750ED) and 76 g of distilled water was prepared. 47.6 g of mixed solution 2 of 4.76 g of toluene-2,4-diisocyanate and 42.84 g of acetone was prepared.
[0081] Next, the same flask as in Preparation Example 1 was prepared. 40 g of water-absorbent resin particles B1 and 480 g of n-heptane were added to the flask to obtain a dispersion. Mixed solution 1 was added to the dispersion, and stirred at room temperature for 30 minutes. Mixed solution 2 was added, and stirred at room temperature for 120 minutes. A polymerization reaction was successively carried out on the surface of the water-absorbent resin particles B1 to obtain a reactant. Next, the reactant was heated in an oil bath at 125° C., and water and 76 g of acetone were extracted out of the system by azeotropic distillation of n-heptane and water while refluxing n-heptane.
[0082] The flask was then immersed in an oil bath at 125°C to remove (dry) n-heptane, acetone and water to obtain a dried product. The dried product was passed through a JIS standard sieve having a mesh size of 850 μm to obtain 38.2 g of water-absorbent resin particles A1 having a coating layer containing polyurethane.
[0083] (Preparation Example 3)
[0084] The same flask as in Preparation Example 1 was prepared. 250 g of n-heptane, 100 g of water-absorbent resin particles B1 and 20 g of maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., Hi-WAX 1105A) were added to the flask, stirred at 1000 rpm, heated to 85°C and stirred for 10 minutes.
[0085] Then, n-heptane was removed by drying in an oil bath at 125° C. to obtain a dried product. The dried product was passed through a JIS standard sieve having a mesh size of 850 μm to obtain 111.52 g of water-absorbent resin particles A2 having a coating layer containing a maleic anhydride-modified ethylene-propylene copolymer.
[0086] (Preparation Example 4)
[0087] In a 2L round-bottom cylindrical separable flask, 100 g of water-absorbent resin particles B1 and 5.0 g of Nipsil (Tosoh Silicone Chemical Co., Ltd., item number: SS-30P) as hydrophobic silica were added. Then, using a silicon anchoring wing, the mixture was dispersed at a rotation speed of 150 rpm while immersed in an oil bath at 125°C, and mixed for 20 minutes while maintaining the internal temperature at 100°C.
[0088] Then, the 125°C oil bath was removed from the round-bottom flask, and the temperature inside the round-bottom flask was cooled to room temperature while stirring with a silicon anchor wing to obtain a precursor of coated resin particles. The precursor was passed through a JIS standard sieve with a mesh size of 850 μm to obtain 102.21 g of water-absorbent resin particles A3 having a coating layer containing hydrophobic silica.
[0089] (Preparation Example 5)
[0090] An absorbent mixture consisting of water-absorbent resin particles and pulp was extracted from a diaper for children sold in the Japanese domestic market (Unicharm Co., Ltd., trade name: moony air fit, size L, tape type). Then, the pulp was removed from the absorbent mixture to obtain about 40 g of water-absorbent resin particles B2.
[0091] (Preparation Example 6)
[0092] An absorbent mixture consisting of water-absorbent resin particles and pulp was extracted from a diaper for children sold in the Japanese domestic market (Kao Corporation, trade name: Merries Instant Breathable, L size, tape type). Then, the pulp was removed from the absorbent mixture to obtain about 42 g of water-absorbent resin particles B3.
[0093] (Preparation Example 7)
[0094] 101.75 g of water-absorbent resin particles B4 having a coating layer containing amorphous silica were obtained in the same manner as in Preparation Example 4 except that the hydrophobic silica was changed to Tokusil (Ryoanto Chemical Co., Ltd., item number: NP-S) as the hydrophilic silica.
[0095] (Preparation Example 8)
[0096] The same flask as in Preparation Example 1 was prepared. 293 g of n-heptane and 0.736 g of maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., Hi-WAX 1105A) as a dispersant were added to the flask for mixing. The mixture in the flask was stirred at 300 rpm, the temperature was raised to 80° C., the dispersant was dissolved in n-heptane, and the resulting solution was cooled to 50° C.
[0097] 92.0 g of an 80.5 mass % acrylic acid aqueous solution (acrylic acid: 1.03 mol) as a water-soluble ethylenically unsaturated monomer was added to a beaker having an internal volume of 300 mL, and 147.7 g of a 20.9 mass % sodium hydroxide aqueous solution was dripped into the beaker while cooling from the outside to neutralize 75 mol % of the acrylic acid. Then, 1.376 g of hydroxyethyl cellulose (Sumitomo Seika Co., Ltd., HEC AW-15F) as a thickener, 0.0184 g (0.068 mmol) of potassium persulfate as a radical polymerization initiator, 0.0920 g (0.339 mmol) of 2,2'-azobis(2-methylpropionamidine) dihydrochloride as a water-soluble azo polymerization initiator, and 0.0101 g (0.057 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were added and dissolved to prepare a first-stage aqueous solution.
[0098] The aqueous solution of the first stage is added to the separable flask as described above, and then stirred for 10 minutes. Next, a surfactant solution prepared by dissolving 0.736 g of sucrose stearate (Mitsubishi Chemical Foods Co., Ltd., Ryoto Sugar Ester, S-370, H LB: 3) as a surfactant in 6.62 g of n-heptane is added to the flask to obtain a reaction solution. The reaction solution is stirred at a stirrer speed of 400 rpm while the system is fully replaced with nitrogen. Then, the flask is immersed in a water bath at 66°C to heat the reaction solution, and the polymerization reaction is carried out for 60 minutes while maintaining the temperature at 56°C, thereby obtaining a first-stage polymerization slurry.
[0099] Next, the flask was immersed in an oil bath set at 125°C while stirring at 1000 rpm, and 108.12 g of water was extracted out of the system by azeotropic distillation of n-heptane and water. Then, 4.60 g (0.528 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a surface crosslinking agent was added to the flask, and the mixture was kept at 83°C for two hours.
[0100] Then, the flask was immersed in an oil bath at 125° C. to remove (dry) the n-heptane to obtain polymer particles (dried product). The polymer particles were passed through a JIS standard sieve having a mesh size of 850 μm to obtain 99.95 g of water-absorbent resin particles B5.
[0101] [Evaluation of water-absorbent resin particles]
[0102] The water-absorbent resin particles were subjected to the following evaluations.
[0103] (1)Water retention capacity
[0104] The water retention capacity of water-absorbent resin particles in physiological saline (room temperature) was measured in the following procedure. First, a cotton bag (broad-width cotton cloth No. 60, 100 mm in width × 200 mm in length) weighing 2.0 g of water-absorbent resin particles was placed in a beaker with an internal volume of 500 mL. 500 g of physiological saline was poured into the cotton bag containing the water-absorbent resin particles at once in a manner that did not cause lumps, and the upper part of the cotton bag was tied with tape and allowed to stand for 30 minutes to allow the water-absorbent resin particles to swell. After 30 minutes, the cotton bag was dehydrated for 1 minute using a dehydrator (manufactured by Kokusan Co., Ltd., item number: H-122) with a centrifugal force set to 167 G, and the mass Wa [g] of the cotton bag containing the swollen gel after dehydration was measured. The same operation was carried out without adding water-absorbent resin particles, and the empty mass Wb [g] of the cotton bag when wet was measured, and the water retention capacity of water-absorbent resin particles in physiological saline was calculated by the following formula.
[0105] Water retention [g / g] = (Wa-Wb) / 2.0
[0106] (2) Water absorption rate based on the Vortex method
[0107] 50.0 g of physiological saline was added to a 100 mL beaker equipped with a rotor (8 mm × 30 mm, without ring) and maintained at 25°C in a thermostatic chamber. Next, 2.0 g of the water-absorbent resin particles for evaluation were added to the vortex of the physiological saline stirred at 600 rpm, and a stopwatch was started at the same time. The time when the vortex disappeared and the liquid surface became flat was taken as the end point, and the time (seconds) to the end point was taken as the water absorption rate.
[0108] (3) Non-pressurized DW
[0109] use Figure 2 The non-pressurized DW of the water-absorbent resin particles is measured by the measuring device Z shown in FIG. The measuring device Z includes a dropper 71, a conduit 72, a flat measuring table 73, a nylon mesh 74, a stand 75, and a clamp 76. The dropper 71 includes a dropper 71a having a scale, a rubber stopper 71b sealing the upper opening of the dropper 71a, a cock 71c connected to the lower front end of the dropper 71a, an air introduction pipe 71d connected to the lower part of the dropper 71a, and a cock 71e. The dropper 71 is fixed by a clamp 76. The measuring table 73 has a through hole 73a with a diameter of 2 mm formed in the center thereof, and is supported by a stand 75 with a variable height. The through hole 73a of the measuring table 73 and the cock 71c of the dropper 71 are connected by a conduit 72. The inner diameter of the conduit 72 is 6 mm.
[0110] The measurement is performed under an environment of a temperature of 25°C and a humidity of 50±10%. First, close the stopcock 71c and the stopcock 71e of the dropper part 71, and put the physiological saline 77 adjusted to 25°C into the dropper 71a from the opening at the top of the dropper 71a. After sealing the opening of the dropper 71a with a rubber stopper 71b, open the stopcock 71c and the stopcock 71e. Fill the inside of the catheter 72 with the physiological saline 77 to prevent air bubbles from entering. Adjust the height of the measuring table 73 so that the water level of the physiological saline 77 reaching the through hole 73a is the same as the upper surface height of the measuring table 73. After adjustment, read the water level of the physiological saline 77 in the dropper 71a using the scale of the dropper 71a, and use its position as the zero point (the reading value at 0 seconds).
[0111] A nylon mesh 74 (40 mm×40 mm, 250 meshes, thickness: about 50 μm) is laid near the through hole 73a on the measuring table 73, and a cylinder with an inner diameter of 30 mm and a height of 20 mm is placed in the center thereof. 1.00 g of water-absorbent resin particles 78 are uniformly dispersed in the cylinder, and then the cylinder is carefully removed to obtain a sample in which the water-absorbent resin particles 78 are dispersed in a circular shape in the center of the nylon mesh 74. Next, the nylon mesh 74 carrying the water-absorbent resin particles 78 is moved quickly to a degree that the water-absorbent resin particles 78 do not escape, so that the center is located at the position of the through hole 73a, and the measurement is started. The moment when the air bubble is first introduced from the air introduction tube 71d into the dropper 71a is regarded as the start of water absorption (0 seconds).
[0112] The amount of the physiological saline 77 reduced in the dropper 71a (i.e., the amount of the physiological saline 77 absorbed by the water-absorbent resin particles 78) is read in units of 0.1 mL, and the amount of the physiological saline 77 reduced 5 minutes after the water-absorbent resin particles 78 start to absorb water is read Wc [g]. The 5-minute value of the non-pressurized DW is calculated from Wc by the following formula. The non-pressurized DW is the amount of water absorbed per 1.00 g of the water-absorbent resin particles 78.
[0113] DW value without pressure [mL / g] = Wc / 1.00
[0114] Table 1
[0115] Preparation Example Water-absorbent resin particles Water retention capacity (g / g) Water absorption speed (seconds) Unpressurized DW (mL / g) 1 B1 43 40 54 2 A1 22 67 2 3 A2 35 61 33 4 A3 38 82 15 5 B2 36 25 46 6 B3 37 53 38 7 B4 37 34 60 8 B5 42 153 9
[0116] [Preparation of absorbent body]
[0117] Using an airflow type mixing device (manufactured by Otec Co., Ltd., Padformer), water-absorbent resin particles in the amounts (g) shown in Table 2 or Table 3 and 8.0 g of crushed pulp (manufactured by Rayonier Co., Ltd., Rayfloc) were uniformly mixed by air papermaking to form an absorbent core of 40 cm × 12 cm in size. 2The absorbent is placed on a paper towel of 16 g / m2, and 0.6 g of the absorbent is sprayed using a sprayer with ion exchange water added thereto. 2 A paper towel of 200 mm was placed on the absorbent to prepare a laminate. A metal mesh of 42 cm × 22 cm with a mesh size of 2 mm was placed on the laminate, and a press machine (small pneumatic press machine, Imoto Seisakusho) was used to press the entire laminate under a load of 141 kPa for 30 seconds, thereby preparing an absorbent having a water-absorbent resin particle content of 60% by mass.
[0118] [Absorbent articles]
[0119] On the upper surface of the absorbent body, a sheet having the same size as the absorbent body and a basis weight of 22 g / m 2 An absorbent article was prepared by placing a breathable porous liquid-permeable sheet made of polyethylene of the same size and basis weight on the lower surface of the absorbent body and sandwiching the absorbent body. The following evaluation was performed using the absorbent article.
[0120] (Preparation of test solution)
[0121] 9866.0 g of distilled water, 100.0 g of sodium chloride, 3.0 g of calcium chloride dihydrate, 6.0 g of magnesium chloride hexahydrate, 25.0 g of a 1 mass % Triton-X solution (a mixture of Triton X-100 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. and water), and 0.25 g of Food Blue No. 1 (for coloring) were mixed to prepare a test solution.
[0122] (Absorption rate)
[0123] The test was conducted in a room adjusted to 25°C and 50% humidity (RH). The absorbent article was placed on a horizontal platform, and a liquid injection cylinder (weight 60 g) with an opening of 3 cm in inner diameter was placed in the center of the absorbent article. Then, 150 mL of the test liquid was quickly injected into the cylinder. The time from the injection of the test liquid until the test liquid was completely absorbed by the absorbent article was measured and set as the absorption rate (seconds).
[0124] (reverse flow)
[0125] Remove the cylinder, and 5 minutes after the test liquid is put in, place about 75g of filter paper (ADVANTEC No.51A, formed into 100mm×100mm) of pre-measured mass near the center of the absorbent article, and quickly place a weight of about 0.7psi (bottom surface 100mm×100mm, 5.0kg) on it, and apply the load for 5 minutes. Then, remove the weight and filter paper, and measure the mass of the test liquid absorbed in the filter paper. The mass increase of the filter paper before and after the test is set as the backflow (g).
[0126] (Diffusion)
[0127] Ten minutes after the test liquid was put in, the distance of the liquid diffused in the absorbent article was measured using a plastic ruler with a length of 50 cm, and this distance was defined as the diffusion length (cm). The diffusion length was measured by peeling off the breathable porous liquid-permeable sheet made of polyethylene from the absorbent article so that the diffused test liquid could be clearly seen. In addition, the diffusion length is the length of a portion of the stain formed on the surface of the absorbent, specifically, the length of the portion of the stain formed on the surface of the absorbent that passes through the test liquid injection portion (the portion corresponding to the center of the cylinder when the test liquid is injected) and extends parallel to the long side of the absorbent.
[0128] Next, a Unipack (manufactured by Japan Co., Ltd., item number: L-4, polyethylene material, size: 480 mm × 340 mm, thickness: 0.04 mm) was cut along the contour of the stain formed on the surface of the absorbent body to prepare a film A (Fa), and the mass was measured. In addition, the same Unipack was used to prepare a film A (Fa) cut into a length of 100 mm × width of 100 mm (area 10000 mm 2 ) of 10 sheets of film B, measure the mass and find the average mass (Fb) of each sheet of film B. Calculate the diffusion area (cm2) in the absorbent article by the following formula: 2 ).
[0129] Diffusion area (cm 2 ) = {(Fa / Fb) × area of Fb (10000mm 2 )} / 100
[0130] Table 2
[0131]
[0132] Table 3
[0133]
[0134] Description of Reference Numerals
[0135] 10: absorbent body 10a, 78: water-absorbent resin particles
[0136] 10b: fiber layer 20a, 20b: core wrapping sheet
[0137] 30: Liquid-permeable sheet 40: Liquid-impermeable sheet
[0138] 71: dropper part 71a: dropper
[0139] 7lb: rubber stopper 71c, 71e: stopcock
[0140] 71d: air introduction tube 72: conduit
[0141] 73: Measuring table 74: Nylon mesh
[0142] 73a: through hole 75: stand
[0143] 76: Clamp 77: Saline
[0144] 100: Absorbent article Z: Measuring device
Claims
1. An absorbent body comprising water-absorbent resin particles, wherein: The water-absorbent resin particles include water-absorbent resin particles A and water-absorbent resin particles B. The water-absorbent resin particles A have a water absorption rate of 55 to 150 seconds according to the Vortex method and a 5-minute value of DW without pressure of 36 mL / g or less. The water-absorbent resin particles B satisfy at least one of the following conditions: a water absorption rate based on the Vortex method of less than 55 seconds, a water absorption rate based on the Vortex method of greater than 150 seconds, or a 5-minute value of the non-pressurized DW of greater than 36 mL / g. The content of the water-absorbent resin particles A is 9% by mass to 90% by mass based on the total amount of the water-absorbent resin particles.
2. The absorbent body according to claim 1, wherein The water-absorbing resin particles A are coated resin particles having a water-insoluble coating layer that covers at least a portion of the surface of the water-absorbing resin particles.
3. The absorbent body according to claim 2, wherein: The coating layer is a layer containing at least one water-insoluble component selected from the group consisting of water-insoluble organic compounds and water-insoluble inorganic compounds.
4. The absorbent body according to claim 3, wherein: The water-insoluble organic compound includes at least one organic compound selected from the group consisting of polyurethane, polyolefin, polyester, polyamide, polystyrene, polycarbonate, polyacrylate, polyacetal, and acid-modified products thereof.
5. The absorbent body according to claim 3, wherein The water-insoluble inorganic compound includes at least one inorganic compound selected from the group consisting of light anhydrous silicic acid, calcium silicate, silicon dioxide, talc, silicon monoxide, and synthetic hydrotalcite.
Citation Information
Patent Citations
Production of highly water absorbing resin
JP1994345819A
Absorbent member for bodily fluids having good wet integrity and relatively high concentration of absorbent polymer forming a hydrogel
JP1997510889A
Absorbent resin particles, absorbent article and production method therefor
WO2020122208A1